FRI0572 LEPTIN-ADJUSTMENT OF THE MULTI-BIOMARKER DISEASE ACTIVITY (MBDA) SCORE REDUCES THE INFLUENCE OF ADIPOSITY. (2nd June 2020) - Baker, J.; Curtis, J.; Chernoff, D.; George, M.
Abstract : Background: Obesity and excess adiposity influence inflammatory markers and bias disease activity assessment, especially among women. A multi-biomarker disease activity (aMBDA) score has been developed to account for the effects of age, sex and adiposity (leptin) and improves prediction of radiographic damage progression. 1 Objectives: 1) Determine if the adjusted measure demonstrates a reduced association with adiposity. 2) Assess the impact of the leptin-adjustment on the score over the range of adiposity. 3) Assess relationships between MBDA scores and clinical disease activity. Methods: Patients with rheumatoid arthritis (RA), ages 18-75 years, completed whole-body dual-energy x-ray absorptiometry to quantify fat mass indices (FMI, kg/m 2 ). Age-, sex-, and race-specific Z-Scores were calculated based on the distributions in a healthy reference population. Disease activity was assessed with the CDAI and swollen joint count (SJC). Baseline van der Heijde-Sharpe (vdHS) scores were determined by a radiologist. MBDA assays were performed on stored serum samples. Descriptive statistics described relationships between the FMI Z-Score and the MBDA and the aMBDA. Clinical disease activity, SJC, and radiographic damage were also compared across MBDA score categories. Results: Of 104 participants (50% female), the mean (SD) age was 56.1 (12.5) and mean BMI was 28.8 (6.9) (Table 1 ). The unadjusted MBDA score was strongly associated with BMI among women (Women: Rho=0.46 [p< 0.001]; Men: Rho=-0.12), while the aMBDA was not associated with BMI in women and was inversely correlated in men (Women: Rho=0.17; Men: Rho=-0.32 [p=0.02]). The unadjusted MBDA score was also strongly associated with FMI Z-Score among women (Figure; Women: Rho=0.42 [p=0.002]; Men: Rho=-0.10; p=0.01). The aMBDA was not significantly associated with FMI Z-Score (Female: Rho= 0.17; Male: Rho=-0.26). Leptin-adjustment reduced the MBDA score in the highest quartile of FMI in women but not men, and increased the MBDA score in the lowest FMI quartiles in both women and men; these patients in the lowest FMI quartile had the highest median SJC (p=0.05 for men, p=0.78 for women; Figure). The aMBDA reclassified 4 women (8%) and 9 men (17%) into higher disease activity categories and 2 women (4%) and 2 men (4%) into lower categories. CDAI, SJC, and radiographic scores were similar across activity categories for the unadjusted MBDA score and aMBDA (Table 2 ). Conclusion: Leptin-adjustment of the MBDA score reduced bias related to excess adiposity in women with RA. Adjustment results in lower MBDA scores in women with greater adiposity, and higher MBDA scores in women and men with lesser adiposity. The aMBDA may reduce misclassification due to excess adiposity and improve identification of active disease among patients with lower adiposity. High aMBDA scores among men with low adiposity may reflect severe disease or excess comorbidity in this group. References: [1] Curtis et al. Rheumatology (Oxford ) 2018. PMID: 30590790 Disclosure of Interests: Joshua Baker Grant/research support from: Myriad RBM, Consultant of: Bristol-Myers Squib, Burns-White LLC, Jeffrey Curtis Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, David Chernoff Employee of: Myriad, Michael George Grant/research support from: Bristol Myers Squibb, Consultant of: AbbVie